Neonatal meningitis caused by Achromobacter xylosoxidans. - Namnyak, S S (1985)
The clinical and bacteriological findings in a case of neonatal meningitis caused by Achromobacter xylosoxidans are presented. This appears to be only the second report of meningitis caused by this species.